The Far-Reaching Impact of Cluster Environments on the Nuclear Activity and Star Formation of Galaxies - de Vos, Kelly (2025)
This thesis presents interlinked studies on radio and optical observational data, with the aim of understanding environmental effects on the star formation and nuclear activity of galaxies. These studies have been facilitated by the recent availability of large, deep radio surveys, enabling detailed investigations of galaxy properties across diverse environments. By combining these datasets with optical observations, this work explores how local and global environmental processes, such as ram pressure, galaxy density, and cluster-centric distance, influence the evolution of galaxies.